USING FABLE VIDEO ILLUSTRATION AS A MEDIUM FOR VOCABULARY MASTERY AT SMK BAZNAS SULAWESI SELATAN - Andi Raihanah Fatihah Akbarullah Puli; Munir Munir; Amra Ariyani (State University of Makassar, 2023)
The purpose of this study to find out whether or not the use of fable video illustration as a medium improves the student’s vocabulary mastery at SMK Baznas Sulawesi Selatan. Pre-experimental design is a method used by researchers with one group pre-test and post-test. The population in this study were class X nursing students at SMK Baznas Sulawesi Selatan for the 2022/2023 academic year. This research uses cluster random sampling technique. in this case, the researcher chose class X nursing as a representation of the population consisting of 32 students. The results of this study prove that there is a significant difference between student scores before treatment and student scores after treatment. It can be seen from the students' pre-test mean score(47.53) and it is lower than the post-test means (74.75). In addition, by using illustrated video fables, students can remember words, train and be effective in teaching vocabulary at SMK Baznas Sulawesi Selatan. In conclusion, that the use of fable video illustration improves student’s vocabulary mastery at SMK Baznas Sulawesi Selatan acedemic year 2022/2023.Keywords— Fable video illustration, Vocabulary Mastery amd Improvement